KEBIJKAN PEMERINTAH DAERAH KABUPATEN KAMPAR DALAM TATA KELOLA PNS DI KABUPATEN KAMPAR TAHUN 2016 - Rizki, T. Jeani; M, Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to find out how the Local Government Policy in Civil Service Manpower in Kampar District Year 2016 and to find out how the policy of Kampar Regency Government in the governance of Civil State Employees in Kampar District and what are the Constraints of Personnel Agency and Resource Development Human. This research uses qualitative method of penetration with descriptive research type, which can be interpreted as problem-solving process investigated by describing the state of research subjeck based on facts that appear during the research which then continued with based on existing theories. Personnel and Human Resource Development Agency (BKPSDM) Kampar regency is a government agency that has the task of implementing the preparation and implementation of regional policies in the field of personnel and can be assigned to carry out the implementation of authority delegated by the government to the Regent of Kampar Regency as the Government's representative in the framework of deconcentration. Making Human Resources and Human Resource Development Agency of Kampar Regency as a professional and prosperous Coaching and Development Agency for civil servants. Key word : Policy, Governance, Governance Employes